دور البراعة التسويقية في التموقع السوقي دراسة تحليلية لآراء عينة من المديرين في مجموعة ماس القابضة للطاقة اقليم كوردستان العراق - العسكري, أ.د برشنك صالح محمد; بندر, م.م زهرة أسد سيه (Sulaimani Journal for Humanities, 2023)
The research aims to study the marketing ambidexterity and its role in the market positioning in the group of MAS Energy Holding stations in the Kurdistan Region of Iraq, and based on the importance of the research represented in the importance of the researched variables, which is the marketing ambidexterity in its dimensions: (exploiting marketing opportunities, exploring marketing opportunities, marketing flexibility), and market positioning With its dimensions (consumer expectations, product properties, distinction from competitors), a questionnaire was used to collect and analyze data according to the five-point Likert scale (Likert-5), after undergoing virtual validity and stability tests (Alpha Cronbach), to verify its validity, stability and validity in measuring variables. The research community was represented by managers from the heads of departments, who totaled (102) managers in three power stations belonging to the Mass Holding Group. After the end of the distribution process, (53) questionnaires were retrieved, and after sorting and examination processes, two forms were excluded, and the remaining (51) questionnaires became valid for analysis. Statistical, using (SPSS V.23) and (AMOS V.23) programs, the statistics were processed using (SPSS V.23) and (AMOS V.23) programs, to validate the hypotheses and reach the research objectives. The results of the statistical analysis showed the following: There is a significant correlation with Statistically significant between marketing ambidexterity and its dimensions in the market positioning, there is a statistically significant effect of marketing ambidexterity and its dimensions in the market positioning of the Mass Energy Holding Group of stations, a set of recommendations were presented In various related directions, including: Enhancing fuel supplies to the stations belonging to the MAS Energy Group in the three governorates of the region: Sulaymaniyah, Erbil, and Dohuk, with the amount necessary to operate all its turbines that have been stopped for a long time, to enhance energy, fill the deficit with electric energy, and increase per capita share of it, resolving all outstanding problems. Specifically, the settlement of the company's accumulated financial dues owed by the relevant government agencies
Keywords: Marketing ambidexterity Market Positioning Mass Energy Holding Group